The value of emotional intelligence for high performance coaching - A commentary - O'Neil, D. A. (International Journal of Sports Science and Coaching, 2011)
This commentary focuses on two related themes from Chan`s and Mallett`s article, empathy and emotional contagion. A foundational task for high-performance coaches is the establishment of trusting relationships with their athletes. The emotional intelligence competency empathy is a key factor in understanding and managing relationships. Without practicing empathy coaches cannot develop and nurture strong relationships with their athletes. Coaches that do not have strong relationships with their athletes will be less effective in motivating and encouraging their best performances.